2005
DOI: 10.1177/0033688205053480
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Beliefs about Internationally-Published Materials: A Survey of Tertiary English Teachers in Indonesia

Abstract: This study investigated the beliefs of tertiary teachers in Indonesia about internationally-published materials. In addition, it explored whether there were mismatches between the teachers’ beliefs and what they claimed to be their classroom practices. This study learned that most respondents believed that internationally-published materials were preferable to those published locally. Most respondents indicated that the material from English-speaking countries1 was preferred because they used ‘perfect’ English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 11 publications
2
40
0
2
Order By: Relevance
“…Learners' concerns and calls are reminiscent of Nation and Macalister's (2010) argument that "The material in a course needs to be presented to learners in a form that will help learning" (p. 9), of Cunningsworth's (1995) warnings for teachers that using "dull and uninspiring material" (p. 1) may make learners lose interest and the learning process seem unpleasant, and of Tomlinson's (2012) observation that "In attempting to cater for all students at a particular age and level, global coursebooks often end up not meeting the needs and wants of any" (p. 158). Learners' concerns, therefore, seem to be convincing from a scholarly-driven point of view, but may be rather unwillingly taken up by teachers who generally prefer teaching materials that are internationally-designed by native speaking developers (see, for example, Zacharias, 2005). Learners in this study also call for the integration of other teaching aids such as technological tools that were found to provide invaluable assistance to teachers and learners in developing language fluency, particularly pronunciation (see, for example, AbuSeileek, 2007;Elimat & AbuSeileek, 2014;Luo, 2014;Neri, Mich, Gerosa, & Giuliani, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Learners' concerns and calls are reminiscent of Nation and Macalister's (2010) argument that "The material in a course needs to be presented to learners in a form that will help learning" (p. 9), of Cunningsworth's (1995) warnings for teachers that using "dull and uninspiring material" (p. 1) may make learners lose interest and the learning process seem unpleasant, and of Tomlinson's (2012) observation that "In attempting to cater for all students at a particular age and level, global coursebooks often end up not meeting the needs and wants of any" (p. 158). Learners' concerns, therefore, seem to be convincing from a scholarly-driven point of view, but may be rather unwillingly taken up by teachers who generally prefer teaching materials that are internationally-designed by native speaking developers (see, for example, Zacharias, 2005). Learners in this study also call for the integration of other teaching aids such as technological tools that were found to provide invaluable assistance to teachers and learners in developing language fluency, particularly pronunciation (see, for example, AbuSeileek, 2007;Elimat & AbuSeileek, 2014;Luo, 2014;Neri, Mich, Gerosa, & Giuliani, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One of the shortcomings of Sifakis and Sougari's research was that observations of classroom practices were not included. As previous research has demonstrated, teachers' stated beliefs and actual classroom practices may frequently differ (Basturkmen, Loewen, & Ellis, 2004;Collie Graden, 1996;Zacharias, 2005); thus, inclusion of observed teaching is important to gain a better understanding of the relationship between the two and to determine why these divergences may occur. In a study conducted in Turkey (Phipps & Borg, 2007), which involved both interview and observation data of teachers in a DELTA (Diploma in English Language Teaching to Adults) course, research revealed additional insight into the area of oral error correction.…”
Section: The Powerful Influence Of Teachers' Cognitions On Classroom mentioning
confidence: 99%
“…Somewhat fewer studies have focused on the teaching of reading (El-Okda, 2005;Johnson, 1992) and writing (Burns, 1992;Farrell, 2006). Few TC studies have examined vocabulary teaching (Zhang, 2008), the use of instructional materials (Zacharias, 2005), uses of technology (Lam, 2000), the effects of either teachers' previous language-learning experience (Ellis, 2006) or their language-teaching experience (Gatbonton, 2008). Most striking to us as teacher-researchers interested in enhancing the pronunciation intelligibility of L2 speakers of English is that TC research is even less developed in the domain of L2 pronunciation instruction than in many of the other domains listed above.…”
Section: Introductionmentioning
confidence: 99%